Effects of chitosan nanoparticles with long synthetic siRNAs targeting VEGF in triple-negative breast cancer cells - CÖMEZ, BİRNUR (My University, 2023)
Vascular endothelial growth factor (VEGF) is an essential angiogenic factor in breast cancer development and metastasis. Small interfering RNAs (siRNAs) can specifically silence genes via the RNA interference pathway, therefore were investigated as cancer therapeutics. In this study, we investigated the effects of siRNAs longer than 30 base pairs (bp) loaded into chitosan nanoparticles in triple-negative breast cancer cells, compared with conventional siRNAs. 35 bp long synthetic siRNAs inhibited VEGF gene expression by 51.2% and increased apoptosis level by 1.75-fold in MDA-MB-231 cell lines. Furthermore, blank and siRNA-loaded chitosan nanoparticles induced expression of IFN-γ in breast cancer cells. These results suggest that long synthetic siRNAs can be as effective as conventional siRNAs, when introduced into cells with chitosan nanoparticles.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; General Pharmacology, Toxicology and Pharmaceutics; Breast cancer; Chitosan; Nanoparticle; siRNA; VEGF